1987
DOI: 10.1111/j.1469-8137.1987.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF LOW TEMPERATURE ON DIEL PATTERNS OF CARBOHYDRATE METABOLISM IN LEAVES OF POA ANNUA L. AND POA×JEMTLANDICA (ALMQ.) RICHT.

Abstract: SUMMARYThe effect of low temperature on diel changes in net gas exchange, carbohydrate content and export, and on the extractable activities of sucrose phosphate synthase and acid invertase from leaves of Poa annua (a ruderal grass) and Poa xjemtlandica (a subarctic grass) was investigated. Exposure for 5 d to a temperature of 7 °C significantly reduced the rate of net photosynthesis of P. annua but had no effect that of P. xjemtlandica. In both species, soluble sugars constituted 20 % of the dry weight and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The two primary functions of a source leaf are to fix energy during photosynthesis and export that chemical energy to the rest of the plant (Wardlaw 1990, Geiger and Servaites 1994, Leonardos and Grodzinski 2001). The importance of measuring export rates in the light period during stressful episodes has been noted by several groups (Borland and Farrar 1987, Farrar 1988, Geiger and Servaites 1994, Leonardos and Grodzinski 2001). The daily export patterns of the acclimated and stressed wheat leaves (Figs 2 and 4) show that at all conditions more 14 C‐assimilates were exported in the light during photosynthesis than in the dark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two primary functions of a source leaf are to fix energy during photosynthesis and export that chemical energy to the rest of the plant (Wardlaw 1990, Geiger and Servaites 1994, Leonardos and Grodzinski 2001). The importance of measuring export rates in the light period during stressful episodes has been noted by several groups (Borland and Farrar 1987, Farrar 1988, Geiger and Servaites 1994, Leonardos and Grodzinski 2001). The daily export patterns of the acclimated and stressed wheat leaves (Figs 2 and 4) show that at all conditions more 14 C‐assimilates were exported in the light during photosynthesis than in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular and intercellular movements of photoassimilates from the site of production to the main vascular channels can be inhibited reducing phloem loading and end‐product removal from the leaf (Webb 1970, Farrar 1988, van Bel 1993, Schrier et al 2000). However, few measurements exist that quantify the extent to which changes in temperature alter photosynthesis and concurrent export of newly fixed C from source leaves via the phloem (Borland and Farrar 1987, Jiao and Grodzinski 1996, 1998, Leonardos et al 1996, Grodzinski et al 2001, Leonardos and Grodzinski 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the rapid turnover of storage earbohydrate in slow-growing montane grasses may be crucial in maintaining a pool of soluble sugars in an envirotiment where photosynthesis is unpredictable (Atkinson & Farrar, 1983). Exposure to low temperature resulted in a significantly greater increase in fructan concentration in the leaves of P. x jemtlandiea than in P. annua (Borland & Farrar, 1987). Thus, the rapid turnover of fructans in the leaves of P. x jemtlandiea growing at 19°C may facilitate a more rapid response in fruetan metabolism to any treatment whieh afl"eets the growth of the plant than is possible in P. annua.…”
Section: The Model Of Carbon Partitioningmentioning
confidence: 97%